Geometric systematic prostate biopsy. Issue 2 (4th March 2017) - Chang, Doyoung; Chong, Xue; Kim, Chunwoo; Jun, Changhan; Petrisor, Doru; Han, Misop; Stoianovici, Dan
Abstract: Objective: The common sextant prostate biopsy schema lacks a three-dimensional (3D) geometric definition. The study objective was to determine the influence of the geometric distribution of the cores on the detection probability of prostate cancer (PCa). Methods: The detection probability of significant (>0.5 cm 3 ) and insignificant (<0.2 cm 3 ) tumors was quantified based on a novel 3D capsule model of the biopsy sample. The geometric distribution of the cores was optimized to maximize the probability of detecting significant cancer for various prostate sizes (20–100cm 3 ), number of biopsy cores (6–40 cores) and biopsy core lengths (14–40 mm) for transrectal and transperineal biopsies. Results: The detection of significant cancer can be improved by geometric optimization. With the current sextant biopsy, up to 20% of tumors may be missed at biopsy in a 20 cm 3 prostate due to the schema. Higher number and longer biopsy cores are required to sample with an equal detection probability in larger prostates. Higher number of cores increases both significant and insignificant tumor detection probability, but predominantly increases the detection of insignificant tumors. Conclusion: The study demonstrates mathematically that the geometric biopsy schema plays an important clinical role, and that increasing the number of biopsy cores is not necessarily helpful.